Investigating the Physicochemical Properties of B12X122− (X = H, F, Cl, Br, I) - Lim, Su Ji (University of Waterloo, 2019)
This thesis focuses on B12X122– (X = H, F, Cl, Br, I) experimentally and computationally to understand the fundamental behaviour of this multiply charged anion (MCA) in the gas and solution phases. The thesis explores three different phases of B12X122–: gas phase, micro-solvated phase, and solution phase. This allows for the breakdown of the phenomena affecting the stability of the MCA in solution into the MCAs geometric and electronic properties and solvent-binding interactions. The first study investigates the dynamic clustering behaviour between B12X122– (X = H, F) and solvent molecules in the gas phase. Differential mobility spectrometry (DMS) is used to induce micro-solvation states of the MCA as an approach to bridge the gas and solution phase properties. DMS is coupled with computational studies to draw connections from the microsolvation states and solvent interaction potentials. This will provide a means to investigate the dominance of the effects of the individual interactions on stability of the dianion. The second project explores the bare anion of B12X122– (X = H, F, Cl, Br, I) in the gas phase. Photoelectron spectroscopy (PES) is simulated and compared with the experimental data for a great understanding of the vibronic transitions and electronic structure of the dianion and its monoanionic counterpart. Geometric distortions after electron detachment are also simulated to determine geometric effects on the stability of the B12X122–. Additionally, various computational methods are explored to investigate their accuracy in predicting the MCA’s electronic structure. The solution phase behaviour of B12F122– is explored in the final chapter, coupling the findings with the knowledge gained in the first two projects. The solvated B12F122–aq is studied using femtosecond pump probe absorption spectroscopy to investigate the role of charge-transfer-to solvent in stabilizing the MCA. The investigations detailed in this thesis reveal the intricacies of the electronic and geometric structures of the species in the gas and solution phases. It is concluded that as repulsive Coulombic factors along with solvent interactions determine the stability of the ground and electronic excited states of the MCA in solution phase.
Keywords: Differential mobility spectrometry; Photoelectron spectroscopy; Mass spectrometry; Gas phase; Solution phase; Electronic structure; Charge transfer to solvent; Density functional theory; Boron clusters